Environmental Kuznets Curve for Extended Brics Economies: Do Women Governance and Water Stress Matter? - Caporin, Massimiliano; Shahbaz, Muhammad; Kuziboev, Bekhzod; Masharipova, Manzura; Allaberganov, Sherali; Makhmudov, Samariddin (International Journal of Energy Economics and Policy, 2024)
Environmental Kuznets Curve (EKC) for extended BRICS is examined by considering different shapes such as liner, U-and N-shaped, and the impact of women’s governance and water stress. To calculate cointegrating regressions, a Fully Modified Ordinary Least Squares (FMOLS) is applied, and the estimated long-term relations are included in a panel Vector Error Correction model. Moreover, Methods of Moments of Quantile Regression (MMQR) is run to robust the findings. The FMOLS results indicate the validation of the linear EKC association for extended BRICS compared to other relations, the U- and N-shaped. This is attributed to the reason that the extended BRICS nations are in the earlier stages of the EKC. It is observed that per capita gross domestic product increases CO2 emissions in the long term, whereas women’s governance and water stress decrease CO2 emissions in the long term in extended BRICS. Furthermore, there exists a causal association between per capita GDP, women’s governance, water stress, and CO2 emissions. MMQR results also validate the negative association between CO2 emissions, women governance and water stress across all the quantiles, 10%-90%.